Adipokine Levels of RBP4, Resistin and Nesfatin-1 in Women Diagnosed With Gestational Diabetes - Kučerová, V; Karásek, D; Krystyník, O; Štefaničková, L; Němeček, V; Friedecký, D (Physiological research, 2024)
Gestational diabetes mellitus (GDM) is a common complication of pregnancy in which women without previously diagnosed diabetes develop chronic hyperglycemia during pregnancy. It is associated with a number of maternal and fetal/neonatal complications. The role of the adipokines retinol binding protein-4, resistin and nesfatin-1 in the development of GDM is relatively poorly understood, but their role in glucose metabolism is suspected and their use as early markers to predict the development of GDM is being sought. The aim of study was to determine the correlation between the levels of selected adipokines (retinol binding protein-4, resistin, nesfatin-1) in women with gestational diabetes mellitus (GDM) and healthy pregnant women and to compare their levels with other clinical and biochemical parameters. Patients with GDM had significantly higher BMI (28.4±4.5 vs. 24.6±4 kg/m2), total cholesterol (6±1.3 vs. 5.3±1.4 mmol/l) and triacylglycerols (1.9±0.8 vs. 1.4±0.7 mmol/l) than women in the control group. RBP4 confirms the significant difference between the groups, it is higher in the control group of healthy pregnant women. The adipokines resistin and nesfatin-1 show no differences between the control and GDM groups, but their ratios with BMI, cholesterol and triacylglycerols, resistin shows elevated levels in the control group. In women with GDM, RBP4 was significantly positively correlated with C-peptide and negatively correlated with total, LDL, and non-HDL cholesterol. Resistin was also negatively correlated with total, LDL, HDL, and non-HDL cholesterol. Nesfatin-1 was only moderately positively correlated with glycated hemoglobin (HbA1C) and fasting glycemia. There is ambiguity in the results of previous studies on the levels of the investigated adipokines in pregnant women with GDM and the interpretation depends on many factors. Keywords: Gestational diabetes, Adipokines, Retinol-binding protein 4, Resistin, Nesfatin-1.
Keywords: biologické markery; plazmatické proteiny vázající retinol; resistin; Resistin; Biomarkers; Pregnancy; krevní glukóza; těhotenství; Adult; Case-Control Studies; dospělí; DNA vazebné proteiny; Retinol-Binding Proteins, Plasma; Diabetes, Gestational; lidé; nukleobindiny; gestační diabetes; ženské pohlaví; studie případů a kontrol; Humans; Calcium-Binding Proteins; proteiny vázající vápník; Adipokines; Nucleobindins; Female; Blood Glucose; adipokiny; DNA-Binding Proteins